A The Influence Of Procyclical, PSAK 71, Audit Quality On Earnings Management With Leverage Variables As Moderation : (Case Study: Banking Companies in Indonesia) - Aprilya Dwi Yandari; Isnani Yuli Andini (International Journal of Economics, Business and Innovation Research, 2024)
The Covid-19 pandemic has brought about many changes in several aspects, especially in the economic sector. The country of Indonesia has experienced a pandemic since the beginning of 2020, due to this outbreak, economic activities, especially companies, have really felt the impact, especially the banking sector. If we look at it from an economic perspective, the existence of procyclical behavior with a slowing economic rate indicates that the level of economic growth is in a contraction phase. Therefore, if viewed based on business cycle theory, procyclical will explain the relationship between economic conditions in a country, so that economic conditions will later influence company (banking) performance. The existence of procyclicals will later be able to influence the occurrence of management behavior in committing deviations, such as increasing market returns or committing fraud in obtaining the desired profit in response to market interest in investing. In this research, researchers used quantitative research using the eviews tool using multiple linear regression tests and moderated regression analysis. This research also uses a sample of 36 banking sector companies in 2020-2022 that are listed on the IDX. The results of this research are procyclical, PSAK 71, Audit Quality has no effect on earnings management. And the leverage variable is unable to moderate procyclical, PSAK 71, Audit Quality on earnings management.